Comparison of the Active Drag and Passive Drag Coefficients at the same Swimming Speed Through Experimental Methods - Lopes, Tiago J. (2025)
Studies about drag in swimming usually report or put the focus on its absolute value. However, it is being claimed that the drag coefficient better represents the hydrodynamic profile of a swimmer. Drag is strongly dependent on speed. Thus, increases in speed will lead to increases in drag. This could lead to misleading interpretations since drag is the water resistance that makes the swimmers’ displacement difficult. Conversely, the drag coefficient is less dependent on speed, which can be seen as a more appropriate measure of the swimmers’ hydrodynamic profile. This study used a complete experimental methodology (experimental and cross-sectional study) to determine the resistive forces in crawl swimming at the same speed (i.e., 1.00, 1.05, 1.10 m/s, etc.). In 10 proficient non-competitive adult swimmers (seven men and three women), the drag coefficient (CD ) was compared and the difference between using the technical drag index (TDI) with drag (D, passive or active) or with its respective CD 's. Measurements of active drag (DA ), passive drag (DP ) and CD (CDA and CDP ) were carried out. The TDI was calculated as a measure of swimming efficiency and the frontal surface area (FSA) obtained in active conditions. The active FSA was 20.73 ± 5.56% greater than the passive FSA (large effect size), the propulsion was 58.29 ± 69.61% greater than drag and CDA was 24.60 ± 46.55% greater than CDP (moderate effect size). TDI was significantly lower, but with a small effect size when measured with CD values compared to drag. TDID vs TDICD revealed strong agreement (> 80% of plots were within IC95). This study concludes that proficient swimmers presented a CDA greater than the CDP, but with strong agreement between them, probably due to FSA during active conditions. CD data appears to be a more absolute indicator of drag than TDI.